2010
DOI: 10.1086/656334
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Single Nucleotide Polymorphism at the Main Ribavirin Transporter Gene on the Rapid Virological Response to Pegylated Interferon–Ribavirin Therapy in Patients with Chronic Hepatitis C Virus Infection

Abstract: The equilibrative nucleoside transporter 1 (ENT1) is the main protein involved in ribavirin cellular uptake. Polymorphisms at the ENT1 gene may influence ribavirin activity as part of hepatitis C virus (HCV) therapy. A retrospective study was conducted in 109 human immunodeficiency virus (HIV)-infected patients who were infected with HCV genotypes 1 or 4 who had received pegylated interferon (pegIFN)-ribavirin. Single nucleotide polymorphisms (SNPs) at the ENT1 gene were examined using TaqMan 5'-nuclease assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…A polymorphism within the transmembrane domain of human CNT3 has been shown to alter transport specificity for several nucleoside-derived drugs (11,12). Several single-nucleotide polymorphisms (SNPs) within the ENT1 gene (SLC29A1) have been reported (38). One of the SNPs (rs760370A 3 G) correlated with rapid treatment response in HCV patients, further supporting the role of ENT1-mediated RBV uptake in HCV treatment response.…”
Section: Discussionmentioning
confidence: 96%
“…A polymorphism within the transmembrane domain of human CNT3 has been shown to alter transport specificity for several nucleoside-derived drugs (11,12). Several single-nucleotide polymorphisms (SNPs) within the ENT1 gene (SLC29A1) have been reported (38). One of the SNPs (rs760370A 3 G) correlated with rapid treatment response in HCV patients, further supporting the role of ENT1-mediated RBV uptake in HCV treatment response.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanisms underlying the interindividual difference in the hepatic ENT1 activity level remain unclear, but SNPs are promising candidates for the causal factors that result in the difference. Since two intronic SNPs have been revealed to be associated with RVR (and SVR) (12,18), investigations should be conducted to determine whether these SNPs have a positive effect on the hepatic ENT1 expression level.…”
Section: Figmentioning
confidence: 99%
“…In addition, Morello et al (12) reported the association of an intronic single nucleotide polymorphism (SNP) of the SLC29A1 (ENT1) gene with rapid virologic response (RVR; defined as an undetectable serum HCV RNA level at week 4) of treatment of genotype-1 Caucasian patients. More recently, Tsubota and colleagues revealed that another intronic SNP in the SLC29A1 gene is associated with SVR, as well as RVR, in genotype-1 Japanese patients (18).…”
mentioning
confidence: 99%
“…3,4) On the other hand, it has been reported that three SNPs, rs6932345, rs747199 and rs760370, existing on intron of SLC29A1 gene were associated with drug response and mRNA expression with the frequency of >0.1 in Japanese. [5][6][7][8] Tsubota et al recently reported that rs6932345 in SLC29A1, a major RBV transporter gene, was a significant genetic factor associated with the outcome of pegylated-interferon (IFN)/ RBV combination therapy in patients with monoinfected hepatitis C virus (HCV). 5) They found that patients with the rs6932345 AA genotype (wild-type) had a higher rate of rapid and sustained virological response and a higher RBV trough concentration than did patients with the AC/CC genotypes (mutation carrier).…”
mentioning
confidence: 99%
“…Another research group also found that rs760370, an SNP highly linked with rs6932345, was associated with rapid virological response in IFN/RBV therapy for patients co-infected with human immunodeficiency virus and HCV. 5,7) These observations are quite interesting to understand the impact of SLC29A1 activity on IFN/RBV combination therapy, in which SLC29A1 plays an important role in intracellular uptake and gastrointestinal absorption of RBV. 9) Although wild-type rs6932345 may provide higher activity of SLC29A1 than the mutant type, no data have been available on such an association, including data on mRNA expression.…”
mentioning
confidence: 99%